Tom Yum Goong (2005): A Political Reading of an Action Film - Wongchalard, Natawan (Journal of Mekong Societies, 2017)
Action films are often criticized for being populist while having a weak political message. This paper contests this criticism by looking at a popular action film, The Protector, better known in Thai as Tom Yum Goong (2005, dir. Prachya Pinkaew), from a different angle. My analysis of the film, based on the Marxist concept of class, demonstrates that a political message needs not be framed exclusively through filmic dialogue, but also through the figuration of the main characters and the structural dichotomy of the narrative. Within this framework, Tom Yum Goong, while not a political film, can be read politically, thus conveying a political message critical to our (re)consideration of political representation in action films, which are often viewed as mechanisms of political conservatism.